The Estradiol Signalling Pathway in the Marine Polychaete, Capitella Teleta - Murillo Ramos, Andrea (My University, 2024)
The use of estrogen as an endocrine regulator was thought to be restricted to vertebrates until estrogen receptors were discovered in a wide range of invertebrates, raising intriguing questions about the function of estrogen receptors across metazoans. Capitella teleta is a marine lophotrochozoan used as an indicator species for pollution and an emerging model for regeneration and developmental evolutionary studies. In vitro studies using C. teleta have revealed that their estrogen receptor is ligand-activated, specifically by estrogens and not other steroids. This thesis investigated whether the estradiol signalling pathway was present, and its role in development, sexual maturation, and behaviour. I found that estrogen receptors are present at various life stages and sexes in Capitella teleta; but patterns of expression and estrogen levels do not suggest a role in sexual maturation or reproduction. Based on the expression of receptors in the brain, I developed a locomotory behavioural assay in Capitella teleta and identified that estradiol exposure causes hypoactivity in males but not females. I used RNA-seq to investigate gene expression in juveniles and adult males, females, and hermaphrodites to identify genes that may be important in maturation and reproduction. Male-transitioned hermaphrodites were more transcriptionally similar to females than males. I discuss the advantages of using Capitella teleta as a model for labile sexual expression. Overall, the data in this thesis suggest a role for the estradiol signalling in development and behaviour, but not sexual maturation or reproduction. This thesis explores the estradiol signalling pathway and further advances knowledge of the understudied juvenile and adult stages of the emerging model polychaete Capitella teleta.